Resin composition, method for producing resin composition, pellet, molded article, kit, laser welded product, and method for manufacturing laser welded product

JP2025041239APending Publication Date: 2025-03-26GLOBAL POLYACETAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023148415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

Smart Images

  • Figure 2025041239000001
    Figure 2025041239000001
  • Figure 2025041239000002
    Figure 2025041239000002
  • Figure 2025041239000003
    Figure 2025041239000003
Patent Text Reader

Abstract

To provide a resin composition which is excellent in flame retardancy and shielding property, and enables laser welding, and a method for producing a resin composition, a pellet, a molded article, a kit, a laser welded product, and a method for manufacturing a laser welded product.SOLUTION: A resin composition for laser welding contains a polyamide resin, a maleic acid anhydride-modified polyphenylene ether-based resin, a phosphazene-based flame retardant, a zinc metal oxide, and a dye having a perylene skeleton, where transmittance at a wavelength of 940 nm, which is measured according to ISO 13468-2 when the resin composition is molded to 1 mm thickness, is less than 20%, and a light source at a wavelength of 800 to 1,100 nm is used.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a method for producing the resin composition, pellets, a molded article, a kit, a laser welded article, and a method for producing the laser welded article. In particular, the present invention relates to a resin composition for laser welding containing a polyamide resin as a main component. [Background technology]

[0002] Polyamide resin, a typical engineering plastic, is easy to process and has excellent mechanical properties, electrical properties, heat resistance, and other physical and chemical properties. For this reason, it is widely used in vehicle parts, electrical and electronic equipment parts, and other precision equipment parts. Recently, parts with complex shapes have also been manufactured from polyamide resin. For example, various welding techniques, such as adhesive welding, vibration welding, ultrasonic welding, hot plate welding, injection welding, and laser welding, are used to bond parts with hollow parts such as intake manifolds.

[0003] However, welding with adhesives has problems such as the time loss required for hardening, as well as environmental impact such as pollution of the surrounding area. Problems have been pointed out with ultrasonic welding and hot plate welding, such as damage to products due to vibration and heat, and the need for post-processing due to the generation of wear powder and burrs. Injection welding often requires special molds and molding machines, and furthermore, it cannot be used unless the material has good fluidity.

[0004] On the other hand, laser welding is a method of joining a resin member (hereinafter sometimes referred to as a "light-selectively-transmissive resin member") that is transparent (also referred to as non-absorbent or weakly-absorbent) to laser light in a specific wavelength range to a resin member (hereinafter sometimes referred to as an "absorbent resin member") by contacting and welding the two resin members. Specifically, this method irradiates a laser beam of a specific wavelength from the light-selectively-transmissive resin member side to the joining surface, and melts and joins the absorbing resin member that forms the joining surface with the energy of the laser beam. Laser welding does not generate abrasion powder or burrs, and causes little damage to the product. Furthermore, polyamide resin itself is a material with a relatively high laser transmittance, so processing of polyamide resin molded products using laser welding technology has recently been attracting attention.

[0005] The light-selectively transparent resin member is usually molded from a light-selectively transparent resin composition. Patent Document 1 describes a polyamide resin composition as such a light-selectively transparent resin composition, which contains 25 to 50 mass % of a semi-aromatic polyamide resin, 3 to 20 mass % of a bromine-based flame retardant, 1.5 to 10 mass % of zinc stannate, and a light-transmitting dye. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-012093 A Summary of the Invention [Problem to be solved by the invention]

[0007] Here, the above resin composition has excellent flame retardancy and high light transmittance, but there is a demand for a resin composition having improved flame retardancy using a flame retardant other than a halogen-based flame retardant. Also, when an attempt is made to increase the shielding property, the laser transmittance tends to decrease. The present invention has an object to solve the above problems, and to provide a resin composition that has excellent flame retardancy and shielding properties and is laser weldable, as well as a method for producing the resin composition, pellets, molded products, kits, laser welded products, and a method for producing laser welded products. [Means for solving the problem]

[0008] In view of the above-mentioned problems, the present inventors have conducted studies and have found that the above-mentioned problems can be solved by providing a resin composition containing a polyamide resin, a maleic anhydride-modified polyphenylene ether resin, a phosphazene-based flame retardant, zinc metal oxide, and a colorant having a perylene skeleton. Specifically, the above problems were solved by the following means. <1> A resin composition comprising a polyamide resin, a maleic anhydride-modified polyphenylene ether resin, a phosphazene-based flame retardant, a zinc metal oxide, and a colorant having a perylene skeleton, wherein the resin composition, when molded into a thickness of 1 mm, has a transmittance at a wavelength of 940 nm as measured in accordance with ISO 13468-2 of less than 20%, and the resin composition is suitable for laser welding using a light source having a wavelength in the range of 800 to 1100 nm. <2> The dye having a perylene skeleton has a naphthylenebenzimidazoperylene skeleton. <1> The resin composition according to claim 1. <3> The polyamide resin comprises a semi-aromatic polyamide resin. <1> or <2> The resin composition according to claim 1. <4> The polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. <1> ~ <3> 10. The resin composition according to claim 9 . <5> the zinc metal oxide comprises zinc borate; <1> ~ <4> 10. The resin composition according to claim 9 . <6> Further containing glass filler, <1> ~ <5> 10. The resin composition according to claim 9 . <7> the dye having a perylene skeleton has a naphthylenebenzimidazoperylene skeleton, the polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, wherein 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; the zinc metal oxide comprises zinc borate; Further containing glass filler, <1> ~ <6> 10. The resin composition according to claim 9 . <8> The method includes preparing a masterbatch of a phosphazene-based flame retardant using a maleic anhydride-modified polyphenylene ether-based resin, and then kneading the masterbatch with a polyamide resin. <1> ~ <7> 13. A method for producing the resin composition according to claim 12. <9> <1> ~ <7> 2. A pellet of the resin composition according to claim 1. <10> <1> ~ <7> 2. A molded article formed from the resin composition according to claim 1. <11> <9> A molded article formed from the pellets according to claim 1. <12> <1> ~ <7> 13. A kit for laser welding using a light source having a wavelength in the range of 800 to 1100 nm, comprising the resin composition according to any one of 1 to 2 above, and a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing dye. <13> <12> 2. A laser welded article formed from the kit described in claim 1. <14> <10> or <11> and a molded article formed from a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing dye, wherein a light source used for the laser welding is a laser having a wavelength in the range of 800 to 1100 nm. Effect of the Invention

[0009] The present invention makes it possible to provide a resin composition that has excellent flame retardancy and shielding properties and is laser weldable, as well as a method for producing the resin composition, pellets, molded products, kits, laser welded products, and a method for producing laser welded products. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified.

[0011] In this specification, unless otherwise specified, the number average molecular weight is a value measured by the following method. The number average molecular weight (Mn) is measured by gel permeation chromatography (GPC) using a standard polymethyl methacrylate (PMMA) equivalent value. Two columns packed with styrene polymers are used as the packing material, and hexafluoroisopropanol (HFIP) with a sodium trifluoroacetate concentration of 2 mmol / L is used as the solvent. The resin concentration is 0.02 mass%, the column temperature is 40°C, the flow rate is 0.3 mL / min, and the measurement is performed using a refractive index detector (RI). In addition, the calibration curve is measured by dissolving six levels of PMMA in HFIP.

[0012] In this specification, the melting point (Tm) is a value measured according to differential scanning calorimetry (DSC) in accordance with ISO11357, unless otherwise specified. A differential scanning calorimeter is used, and the resin is placed in the measurement pan of the differential scanning calorimeter, heated to a temperature above the melting point at a heating rate of 10°C / min under a nitrogen atmosphere, and then rapidly cooled before measurement. The measurement conditions are a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled down to 100°C at a cooling rate of -5°C / min to determine the melting point (Tm). As the differential scanning calorimeter, a "DSC-60" manufactured by SHIMADZU CORPORATION is used.

[0013] If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0014] The resin composition of the present embodiment is a resin composition containing a polyamide resin, a maleic anhydride-modified polyphenylene ether resin, a phosphazene-based flame retardant, zinc metal oxide, and a dye having a perylene skeleton, and is characterized in that the resin composition, when molded to a thickness of 1 mm, has a transmittance of less than 20% at a wavelength of 940 nm as measured in accordance with ISO13468-2, and is a resin composition suitable for laser welding using a light source having a wavelength in the range of 800 to 1100 nm. By adopting such a configuration, it is possible to provide a resin composition that has excellent flame retardancy and shielding properties, and further, is laser weldable. In the resin composition of the present embodiment, a phosphazene-based flame retardant and zinc metal oxide are blended to enhance flame retardancy. However, it has been found that it is difficult to melt-knead the phosphazene-based flame retardant in the polyamide resin. In the present embodiment, it is presumed that the phosphazene-based flame retardant can be melt-kneaded by blending the maleic anhydride-modified polyphenylene ether resin. On the other hand, by blending a dye having a perylene skeleton, the light transmittance of visible light with a wavelength of 700 to 800 nm could be reduced, resulting in a resin composition with excellent shielding properties, while it is presumed that laser welding was achieved by using a light source with a wavelength in the range of 800 to 1100 nm.

[0015] <Polyamide resin> The resin composition of the present embodiment contains a polyamide resin. The type of polyamide resin used in the present embodiment is not particularly limited, and may be an aliphatic polyamide resin or a semi-aromatic polyamide resin, and preferably contains a semi-aromatic polyamide resin. Examples of aliphatic polyamide resins include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 11, polyamide 12, and the like. An example of the semi-aromatic polyamide resin is a polyamide resin that contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and in which 20 to 80 mol % (preferably 30 to 80 mol %, more preferably 40 to 70 mol %) of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit are structural units containing an aromatic ring. By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained resin molded product can be increased. Examples of the semi-aromatic polyamide resin include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 6T / 6I, polyamide 9T, polyamide 10T) and xylylenediamine-based polyamide resins described later.

[0016] In this embodiment, a polyamide resin containing diamine-derived structural units and dicarboxylic acid-derived structural units, in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms (hereinafter sometimes referred to as a "xylylenediamine-based polyamide resin") is preferred.

[0017] The diamine-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 60 mol% or more, even more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, even more preferably 95 mol% or more, and particularly preferably 99 mol% or more, derived from xylylenediamine (preferably paraxylylenediamine and / or metaxylylenediamine).

[0018] The xylylenediamine is preferably paraxylylenediamine and / or metaxylylenediamine. The xylylenediamine preferably contains 0 to 100 mol% metaxylylenediamine and 100 to 0 mol% paraxylylenediamine (however, the sum of metaxylylenediamine and paraxylylenediamine does not exceed 100 mol%), more preferably contains 0 to 90 mol% metaxylylenediamine and 100 to 10 mol% paraxylylenediamine, even more preferably contains 10 to 90 mol% metaxylylenediamine and 90 to 10 mol% paraxylylenediamine, still more preferably contains 20 to 90 mol% metaxylylenediamine and 80 to 10 mol% paraxylylenediamine, still more preferably contains 50 to 90 mol% metaxylylenediamine and 10 to 50 mol% paraxylylenediamine, and even more preferably contains 50 to 80 mol% metaxylylenediamine and 50 to 20 mol% paraxylylenediamine. In the xylylenediamine-based polyamide resin, the total of the constitutional units derived from paraxylylenediamine and the constitutional units derived from metaxylylenediamine preferably accounts for 80 mol % or more, more preferably 85 mol % or more, even more preferably 90 mol % or more, still more preferably 95 mol % or more, still more preferably 98 mol % or more, and still more preferably 99 mol % or more of the constitutional units derived from diamine. The upper limit of the total of the constitutional units derived from paraxylylenediamine and the constitutional units derived from metaxylylenediamine is 100 mol %.

[0019] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0020] On the other hand, the dicarboxylic acid-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 60 mol % or more, even more preferably 70 mol % or more, even more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and particularly preferably 99 mol % or more of α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms. The α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms are more preferably α,ω-straight-chain aliphatic dicarboxylic acids having 9 to 20 carbon atoms, even more preferably α,ω-straight-chain aliphatic dicarboxylic acids having 9 to 14 carbon atoms, even more preferably sebacic acid and / or 1,12-dodecanedioic acid, and even more preferably sebacic acid.

[0021] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are preferably used as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and 1,12-dodecanedioic acid. One or a mixture of two or more of these can be used. Among these, sebacic acid and / or 1,12-dodecanedioic acid are more preferred, with sebacic acid being even more preferred, since the melting point of the polyamide resin falls within a range suitable for molding. A preferred embodiment of the xylylenediamine-based polyamide resin in this embodiment is one in which 50 mol % or more (preferably 70 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid and / or 1,12-dodecanedioic acid (preferably sebacic acid).

[0022] Examples of dicarboxylic acid components other than those mentioned above include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.

[0023] In addition, the xylylenediamine-based polyamide resin is mainly composed of diamine-derived structural units and dicarboxylic acid-derived structural units, but does not completely exclude other structural units, and may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of diamine-derived structural units and dicarboxylic acid-derived structural units is the largest among all structural units among the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of diamine-derived structural units and dicarboxylic acid-derived structural units in the xylylenediamine-based polyamide resin preferably accounts for 90% by mass or more of all structural units, more preferably accounts for 95% by mass or more, even more preferably accounts for 97% by mass or more, and even more preferably accounts for 99% by mass or more.

[0024] The melting point of the xylylenediamine-based polyamide resin is preferably 150°C or higher, more preferably 180°C or higher, and even more preferably 200°C or higher, and is preferably 350°C or lower, more preferably 330°C or lower, even more preferably 300°C, even more preferably 250°C or lower, even more preferably 240°C or lower, even more preferably 230°C or lower, and particularly preferably 225°C or lower.

[0025] The lower limit of the number average molecular weight (Mn) of the xylylenediamine-based polyamide resin is preferably 6,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more, and is preferably 35,000 or less, more preferably 30,000 or less, even more preferably 25,000 or less, and even more preferably 20,000 or less. When it is within such a range, the heat resistance, elastic modulus, dimensional stability, and moldability are improved.

[0026] The content of the polyamide resin in the resin composition of the present embodiment is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, based on 100% by mass of the resin composition. By making it equal to or more than the lower limit, the glass filler content is increased, and high physical properties in terms of rigidity and strength tend to be obtained. In addition, the content of the polyamide resin in the resin composition of the present embodiment is preferably 70% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less, and may be 40% by mass or less, based on the resin composition. By making it equal to or less than the upper limit, the glass filler content is suppressed to a certain extent, and the flowability balance tends to be easily adjusted. The resin composition of the present embodiment may contain only one type of polyamide resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0027] <Maleic anhydride modified polyphenylene ether resin> The resin composition of the present embodiment contains a maleic anhydride-modified polyphenylene ether resin, which allows the phosphazene-based flame retardant to be sufficiently melt-kneaded in the polyamide resin. The maleic anhydride-modified polyphenylene ether resin is a polyphenylene ether resin modified with maleic anhydride. In the present embodiment, the amount of maleic anhydride in the maleic anhydride-modified polyphenylene ether resin is preferably 0.01 to 1.0 mass %, more preferably 0.3 to 0.7 mass %, calculated as the amount of maleic acid. By setting the amount in this range, the obtained molded product can achieve high mechanical strength. The amount of maleic anhydride in the maleic anhydride-modified polyphenylene ether resin refers to the mass of the maleic anhydride used to modify the polyphenylene ether resin and which reacts with the polyphenylene ether resin, converted into the amount of maleic acid.

[0028] Examples of polyphenylene ether resins include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, and poly(2-methyl-6-propyl-1,4-phenylene) ether, with poly(2,6-dimethyl-1,4-phenylene) ether being particularly preferred. The polyphenylene ether resin has an intrinsic viscosity measured in chloroform at a temperature of 30° C. of preferably 0.2 to 0.6 dL / g, more preferably 0.3 to 0.5 dL / g. By making the intrinsic viscosity 0.2 dL / g or more, impact resistance tends to be improved, while by making it 0.6 dL / g or less, moldability and appearance tend to be improved. The intrinsic viscosity within the above range may be adjusted by using two or more polyphenylene ether resins having different intrinsic viscosities in combination.

[0029] In the resin composition of the present embodiment, the mass ratio of the polyamide resin to the maleic anhydride-modified polyphenylene ether resin is preferably 80 / 20 to 60 / 40. In the present embodiment, the mass ratio of the polyamide resin to the maleic anhydride-modified polyphenylene ether resin is more preferably 80 / 20 to 65 / 35, further preferably 80 / 20 to 70 / 30, and further preferably 78 / 22 to 72 / 28. By setting the ratio in this way, the effects of the present invention tend to be more effectively exhibited. The resin composition of the present embodiment may contain only one type of maleic anhydride-modified polyphenylene ether resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0030] In the resin composition of the present embodiment, the total of the polyamide resin and the maleic anhydride-modified polyphenylene ether resin preferably accounts for 90 mass% or more of the thermoplastic resin components contained in the resin composition, more preferably 95 mass% or more, and even more preferably 99 mass% or more. In addition, the total proportion of the thermoplastic resin components (polyamide resin, maleic anhydride modified polyphenylene ether resin, and other resins blended as necessary) in the resin composition is preferably 35 mass% or more, and preferably 40 mass% or more, and is preferably 75 mass% or less, more preferably 65 mass% or less, and even more preferably 55 mass% or less.

[0031] <Phosphazene flame retardants> The resin composition of the present embodiment contains a phosphazene-based flame retardant. By blending the phosphazene-based flame retardant, the flame retardancy of the resin composition can be improved. The phosphazene flame retardant used in this embodiment is an organic compound having a -P=N- bond in the molecule, and is preferably at least one selected from the group consisting of a cyclic phosphazene flame retardant represented by formula (1), a chain phosphazene flame retardant represented by formula (2), and a crosslinked phosphazene flame retardant obtained by crosslinking the phosphazene flame retardant with a crosslinking group. The crosslinking group is preferably an oxygen atom. The crosslinking group is R of the cyclic phosphazene flame retardant (molecule) represented by formula (1). 1 and / or R 2 is the R of another molecule (the cyclic phosphazene flame retardant represented by formula (1)). 1 and / or R 2 and more preferably, bridged by an oxygen atom.

[0032] [ka] In formula (1), a is an integer of 3 to 25; 1 and R 2 may be the same or different and represent an alkyl group, a cycloalkyl group, an alkenyl group, an alkynyl group, an aryloxy group, an amino group, a hydroxy group, an aryl group, or an alkylaryl group.

[0033] [ka] In formula (2), b is an integer of 3 to 10,000; 3 and R 4 may be the same or different and represent an alkyl group, a cycloalkyl group, an alkenyl group, an alkynyl group, an aryloxy group, an amino group, a hydroxy group, an aryl group, or an alkylaryl group. R 5 is -N=P(OR 3 ) 3 groups, -N=P(OR 4 ) 3 groups, -N=P(O)OR 3 Group, -N=P(O)OR 4 R 6 -P(OR 3 ) 4 groups, -P(OR 4 ) 4 groups, -P(O)(OR 3 ) 2 groups, -P(O)(OR 4 ) at least one selected from the following two groups:

[0034] In formula (1) and formula (2), examples of the alkyl group include alkyl groups having 1 to 15 carbon atoms, such as a methyl group, ethyl group, propyl group, isopropyl group, butyl group, t-butyl group, pentyl group, hexyl group, octyl group, decyl group, and dodecyl group. Of these, alkyl groups having 1 to 6 carbon atoms, such as a methyl group, ethyl group, propyl group, isopropyl group, butyl group, t-butyl group, pentyl group, and hexyl group, are preferred, and alkyl groups having 1 to 4 carbon atoms, such as a methyl group, ethyl group, and propyl group, are particularly preferred.

[0035] Examples of the cycloalkyl group include cycloalkyl groups having 5 to 14 carbon atoms, such as cyclopentyl and cyclohexyl groups, and cycloalkyl groups having 5 to 8 carbon atoms are preferred.

[0036] Examples of the alkenyl group include alkenyl groups having 2 to 8 carbon atoms, such as a vinyl group and an allyl group. Examples of the cycloalkenyl group include cycloalkenyl groups having 5 to 12 carbon atoms, such as a cyclopentyl group and a cyclohexyl group.

[0037] Examples of the alkynyl group include alkynyl groups having 2 to 8 carbon atoms, such as ethynyl and propynyl groups, and alkynyl groups having an aryl group as a substituent, such as an ethynylbenzene group.

[0038] Examples of the aryl group include aryl groups having 6 to 20 carbon atoms, such as a phenyl group, a methylphenyl (i.e., tolyl) group, a dimethylphenyl (i.e., xylyl) group, a trimethylphenyl group, and a naphthyl group. Among these, an aryl group having 6 to 10 carbon atoms is preferred, and a phenyl group is particularly preferred.

[0039] Examples of the alkylaryl group include aralkyl groups having 6 to 20 carbon atoms, such as a benzyl group, a phenethyl group, and a phenylpropyl group. Among these, an aralkyl group having 7 to 10 carbon atoms is preferred, and a benzyl group is particularly preferred.

[0040] Among them, R in formula (1) 1 and R 2 , R in Equation (2) 3 and R 4 Preferably, R is an aryl group or an arylalkyl group. By using such an aromatic phosphazene-based flame retardant, the thermal stability of the resin composition can be more effectively improved. From this viewpoint, 1 , R 2 , R 3 and R 4 is more preferably an aryl group, and particularly preferably a phenyl group.

[0041] Examples of the phosphazene-based flame retardants represented by formula (1) or formula (2) include (poly)tolyloxyphosphazenes such as phenoxyphosphazene, o-tolyloxyphosphazene, m-tolyloxyphosphazene, and p-tolyloxyphosphazene, (poly)xylyloxyphosphazenes such as o,m-xylyloxyphosphazene, o,p-xylyloxyphosphazene, and m,p-xylyloxyphosphazene, o,m,p-trimethylphenyloxyphosphazene, and phenoxy Examples of such phosphazenes include (poly)phenoxytolyloxyphosphazenes such as cyclo-o-tolyloxyphosphazene, phenoxy m-tolyloxyphosphazene, and phenoxy p-tolyloxyphosphazene, (poly)phenoxytolyloxyxylyloxyphosphazenes such as phenoxy o,m-xylyloxyphosphazene, phenoxy o,p-xylyloxyphosphazene, and phenoxy m,p-xylyloxyphosphazene, and phenoxy o,m,p-trimethylphenyloxyphosphazene.

[0042] The cyclic phosphazene flame retardant represented by formula (1) is 1 and R 2 Cyclic phenoxyphosphazenes in which a is a phenyl group are particularly preferred. Examples of such cyclic phenoxyphosphazene-based flame retardants include compounds such as phenoxycyclotriphosphazene, octaphenoxycyclotetraphosphazene, and decafenoxycyclopentaphosphazene, which are obtained by removing cyclic chlorophosphazenes such as hexachlorocyclotriphosphazene, octachlorocyclotetraphosphazene, and decachlorocyclopentaphosphazene from a cyclic and linear chlorophosphazene mixture obtained by reacting ammonium chloride with phosphorus pentachloride at a temperature of 120 to 130°C, and then substituting them with a phenoxy group. In addition, the cyclic phenoxyphosphazene-based flame retardant is preferably a compound in which a in formula (1) is an integer of 3 to 8, and may be a mixture of compounds with different a's.

[0043] The average of a is preferably 3 to 5, and more preferably 3 to 4. Among them, a mixture of compounds in which those where a=3 are 50% by mass or more, those where a=4 are 10 to 40% by mass, and those where a=5 or more are 30% by mass or less in total is preferred.

[0044] The chain phosphazene flame retardant represented by formula (2) is R 3 and R 4 A chain phenoxyphosphazene flame retardant in which is a phenyl group is particularly preferred. Examples of such a chain phenoxyphosphazene flame retardant include a compound obtained by ring-opening polymerization of hexachlorocyclotriphosphazene obtained by the above method at a temperature of 220 to 250°C, and substituting the obtained linear dichlorophosphazene having a polymerization degree of 3 to 10,000 with a phenoxy group. In the linear phenoxyphosphazene flame retardant, b in formula (2) is preferably 3 to 1,000, more preferably 3 to 100, and further preferably 3 to 25.

[0045] Examples of the crosslinked phosphazene flame retardant include compounds having a crosslinked structure of a 4,4'-diphenylene group, such as a compound having a crosslinked structure of 4,4'-sulfonyldiphenylene (i.e., a bisphenol S residue), a compound having a crosslinked structure of a 2,2-(4,4'-diphenylene)isopropylidene group, a compound having a crosslinked structure of a 4,4'-oxydiphenylene group, and a compound having a crosslinked structure of a 4,4'-thiodiphenylene group.

[0046] In addition, the crosslinked phosphazene flame retardant is represented by the formula (1): 1 , R 2 a cyclic phenoxyphosphazene flame retardant in which R is a phenyl group and R is crosslinked by the above crosslinking group; or 3 , R 4In terms of flame retardancy, a crosslinked phenoxyphosphazene flame retardant obtained by crosslinking a chain phenoxyphosphazene flame retardant in which R is a phenyl group via the above-mentioned crosslinking group is preferred, and a crosslinked phenoxyphosphazene flame retardant obtained by crosslinking a cyclic phenoxyphosphazene flame retardant via the above-mentioned crosslinking group is more preferred.

[0047] The content of the phosphazene flame retardant in the resin composition of the present embodiment is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and even more preferably 7% by mass or more, and the upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 14% by mass or less, even more preferably 13% by mass or less, and even more preferably 12% by mass or less. The resin composition of the present embodiment may contain only one type of phosphazene flame retardant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0048] The resin composition of the present embodiment is preferably substantially free of flame retardants other than the phosphazene-based flame retardant. Substantially free means that the content of flame retardants other than the phosphazene-based flame retardant is 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, of the blended amount of the phosphazene-based flame retardant.

[0049] <Zinc metal oxide> The resin composition of the present embodiment contains zinc metal oxide. By blending zinc metal oxide, the flame retardancy of the resin composition can be increased. The zinc metal oxide is preferably zinc borate. Zinc borate can be obtained from zinc oxide and boric acid, and examples of the zinc borate include hydrates and anhydrides such as ZnO·B2O3·2H2O and 2ZnO·3B2O3·3.5H2O.

[0050] The zinc metal oxide content in the resin composition of the present embodiment is preferably 3% by mass or more of the resin composition, more preferably 4% by mass or more, even more preferably 5% by mass or more, even more preferably 7% by mass or more, even more preferably 8% by mass or more, and even more preferably 9% by mass or more.The upper limit is preferably 16% by mass or less, more preferably 15% by mass or less, and even more preferably 14% by mass or less. The resin composition of the present embodiment may contain only one type of zinc metal oxide, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range. The resin composition of the present embodiment is preferably substantially free of flame retardant auxiliaries other than zinc metal oxide. Substantially free means that the content of flame retardant auxiliaries other than zinc metal oxide is 10% by mass or less of the blended amount of zinc metal oxide, preferably 5% by mass or less, and more preferably 1% by mass or less.

[0051] <Dyes with perylene skeleton> The resin composition of the present embodiment contains a pigment having a perylene skeleton (sometimes referred to as a "perylene pigment" in this specification). The perylene pigment is preferably a black pigment or a black-purple pigment. The perylene pigment may be a pigment or a dye, but is preferably a pigment. The dye having a perylene skeleton used in this embodiment preferably has a naphthylenebenzimidazoperylene skeleton, more preferably has a 1,8-naphthylenebenzimidazoperylene skeleton, and further preferably is 1,8-naphthylenebenzimidazoperylene. 1,8-naphthylenebenzimidazoperylene is preferably a mixture of cis and trans isomers. The content of the dye having a perylene skeleton in the resin composition of this embodiment is preferably 0.001% by mass or more, more preferably 0.006% by mass or more, and may be 0.018% by mass or more, 0.024% by mass or more, 0.030% by mass or more, or 0.050% by mass or more in the resin composition. The upper limit of the content of the light-transmitting dye is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 1.0% by mass or less, and may be 0.50% by mass or less in the resin composition. The resin composition of the present embodiment may contain only one type of dye having a perylene skeleton, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range. Moreover, the resin composition of the present embodiment preferably does not substantially contain carbon black, which means, for example, that the amount of carbon black is 0.0001 mass % or less of the resin composition. Furthermore, the resin composition of the present embodiment preferably does not substantially contain any light-selective transmitting dye other than the dye having a perylene skeleton. "Substantially does not contain" means, for example, that the content of the light-selective transmitting dye is 0.0001% by mass or less of the resin composition.

[0052] <Glass filler> The resin composition of the present embodiment contains 40 to 95 parts by mass of glass filler relative to 100 parts by mass of polyamide resin. By containing the glass filler, it is possible to achieve high mechanical strength for the obtained molded article. The glass filler that can be used in the resin composition of the present embodiment is preferably surface-treated with a surface treatment agent such as a coupling agent. Glass fillers to which a surface treatment agent is attached are preferred because they have excellent durability, moist heat resistance, hydrolysis resistance, and heat shock resistance.

[0053] The glass filler is composed of a glass composition such as A glass, C glass, E glass, S glass, R glass, M glass, or D glass, and E glass (alkali-free glass) is particularly preferred.

[0054] Examples of the glass filler used in the resin composition of this embodiment include glass fiber, glass flakes, glass plates, glass beads, and the like. Glass fiber and glass flakes are preferred, and glass fiber is more preferred. The glass fiber may be a single fiber or a plurality of single fibers twisted together. The form of the glass fiber may be any of "glass roving" which is a single fiber or a plurality of single fibers twisted together and wound continuously, "chopped strand" which is cut to a length of 1 to 10 mm, and "milled fiber" which is pulverized to a length of 10 to 500 μm. Such glass fibers are commercially available under the trade names "Glaslon Chopped Strand" and "Glaslon Milled Fiber" from Asahi Fiber Glass Co., Ltd. and "E Glass Fiber Chopped Strand" from Nippon Electric Glass Co., Ltd., and are easily available. Glass fibers of different forms can also be used in combination.

[0055] The glass fiber used in this embodiment may have a circular or noncircular cross section. By using glass fiber having a noncircular cross section (particularly flat), warping of the obtained molded product can be more effectively suppressed. In this embodiment, even if glass fiber having a circular cross section is used, warping can be effectively suppressed by using a polyamide resin that crystallizes sufficiently even at a low mold temperature.

[0056] The content of the glass filler in the resin composition of the present embodiment is preferably 40 parts by mass or more, more preferably 45 parts by mass or more, and even more preferably 50 parts by mass or more, relative to 100 parts by mass of the polyamide resin. By making it equal to or more than the lower limit, the unnotched Charpy impact strength tends to be further improved. In addition, the upper limit of the content of the glass filler is 95 parts by mass or less, preferably 80 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 68 parts by mass or less, and even more preferably 65 parts by mass or less, relative to 100 parts by mass of the polyamide resin. By making it equal to or less than the upper limit, a better appearance tends to be maintained.

[0057] The content of the glass filler in the resin composition of this embodiment is, based on 100 mass% of the resin composition, preferably 20 mass% or more, and more preferably 25 mass% or more, and is preferably 60 mass% or less, and more preferably 55 mass% or less, and may further be 53 mass% or less, 50 mass% or less, 45 mass% or less, 40 mass% or less, or 35 mass% or less. The resin composition of the present embodiment may contain only one type of glass filler, or may contain two or more types. When two or more types are contained, the total amount is within the above range. Note that the content of the glass filler in the present embodiment is intended to include the amounts of the sizing agent and the surface treatment agent.

[0058] <Nucleating agent> The resin composition of the present embodiment may contain a nucleating agent. There are no particular limitations on the nucleating agent, so long as it remains unmelted during melt processing and can become a crystal nucleus during the cooling process. Among these, talc and calcium carbonate are preferred, and talc is more preferred. The lower limit of the number average particle size of the nucleating agent is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 3 μm or more.The upper limit of the number average particle size of the nucleating agent is preferably 40 μm or less, more preferably 30 μm or less, even more preferably 28 μm or less, even more preferably 15 μm or less, and even more preferably 10 μm or less.

[0059] The content of the nucleating agent in the resin composition of the present embodiment is preferably 0.01 to 3 mass %, more preferably 0.1 mass % or more, and more preferably 2 mass % or less. The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0060] <Copper iodide, potassium iodide and cerium oxide> The resin composition of the present embodiment preferably contains at least one of copper iodide, potassium iodide, and cerium oxide, and more preferably contains at least one of copper iodide and potassium iodide. By containing copper iodide, the heat resistance and heat aging resistance of the obtained molded article tend to be further improved. In addition, by containing potassium iodide, a complex is easily formed in the polyamide resin, and decomposition of the resin tends to be more effectively suppressed. In other words, by blending these components, it is possible to impart performance according to the application.

[0061] The proportion of copper iodide in the resin composition of this embodiment is preferably 0.01 mass% or more, and more preferably 0.02 mass% or more, and is preferably 2 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, and even more preferably 0.3 mass% or less. The proportion of potassium iodide in the resin composition of this embodiment is preferably 0.01 mass% or more, and more preferably 0.02 mass% or more, and is preferably 2 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, and even more preferably 0.3 mass% or less. The proportion of cerium oxide in the resin composition of this embodiment is preferably 0.01 mass% or more, and more preferably 0.02 mass% or more, and is preferably 2 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, and even more preferably 0.3 mass% or less.

[0062] <Release agent> The resin composition of the present embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and fatty acid amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, and fatty acid amides are preferred, aliphatic carboxylic acids, salts of aliphatic carboxylic acids and fatty acid amides are more preferred, and salts of fatty acid carboxylic acids are even more preferred. For details about the release agent, please refer to paragraphs 0055 to 0061 of JP2018-095706A, the contents of which are incorporated herein by reference. When the resin composition of the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.05 to 3 mass %, more preferably 0.1 to 1 mass %, and even more preferably 0.1 to 0.8 mass %. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0063] <Other ingredients> The resin composition of the present embodiment may contain other components within the scope of the present invention, such as light stabilizers, antioxidants, ultraviolet absorbers, fluorescent brighteners, anti-dripping agents, antistatic agents, anti-fogging agents, anti-blocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. In the resin composition of this embodiment, the contents of the polyamide resin, maleic anhydride-modified polyphenylene ether resin, phosphazene flame retardant, zinc metal oxide, pigment having a perylene skeleton, and other components blended as necessary are adjusted so that the total of the components is 100% by mass. In this embodiment, an embodiment in which the total of the polyamide resin, maleic anhydride-modified polyphenylene ether resin, phosphazene flame retardant, zinc metal oxide, pigment having a perylene skeleton, release agent, and glass fiber accounts for 99% or more by mass of the resin composition is exemplified.

[0064] <Physical properties of resin composition> In the resin composition of the present embodiment, when the resin composition is molded into a thickness of 1 mm, the transmittance at a wavelength of 940 nm measured according to ISO 13468-2 is less than 20%, The lower limit of the transmittance at a wavelength of 940 nm measured according to ISO13468-2 when the resin composition is molded to a thickness of 1 mm is 0% or more. By adopting such a constitution, a molded product having excellent shielding properties can be obtained. Furthermore, the resin composition of the present embodiment, when molded to a thickness of 1 mm, preferably has a transmittance at a wavelength of 1070 nm measured according to ISO 13468-2 of 20% or more, more preferably 40% or more. There is no particular upper limit, but even if it is 50% or less, the required performance is sufficiently satisfied. The light transmittance is measured according to the description in the Examples section below. The resin composition of this embodiment preferably has a flame retardancy of V-0 when molded to a thickness of 0.75 mm and measured according to the UL-94 combustion test. The flame retardancy is measured as described in the Examples section below.

[0065] <Method of producing resin composition> The method for producing the resin composition of the present embodiment is not particularly limited, but a method using a single-screw or twin-screw extruder having a vent port for volatilization as a kneader is preferred. The polyamide resin, the maleic anhydride-modified polyphenylene ether resin, the phosphazene flame retardant, the zinc metal oxide, the dye having a perylene skeleton, and other additives to be mixed as necessary may be fed to the kneader all at once, or the polyamide resin component may be fed, and then the other blending components may be fed sequentially. The glass filler is preferably fed from the middle of the extruder in order to prevent it from being crushed during kneading. Two or more components selected from each component may be mixed and kneaded in advance. In the present embodiment, it is also preferable to prepare a master batch of the phosphazene flame retardant using a maleic anhydride-modified polyphenylene ether resin, and then knead the master batch with a polyamide resin. By adopting such a configuration, the phosphazene flame retardant can be sufficiently dispersed in the polyamide resin. In this embodiment, it is preferable to prepare a master batch of zinc metal oxide together with the phosphazene flame retardant using a maleic anhydride modified polyphenylene ether resin. The amount of the maleic anhydride modified polyphenylene ether resin in the masterbatch is preferably 10 to 50 parts by mass, and more preferably 20 to 45 parts by mass, based on 100 parts by mass of the total amount of the masterbatch. The amount of the phosphazene-based flame retardant in the masterbatch is preferably 10 to 50 parts by mass, and more preferably 20 to 45 parts by mass, when the total amount of the masterbatch is taken as 100 parts by mass. The amount of zinc metal oxide to be made into a master batch is preferably 10 to 50 parts by mass, and more preferably 15 to 40 parts by mass, when the total amount of the master batch contained in the resin composition is taken as 100 parts by mass. The total amount of the master batches does not exceed 100 parts by mass.

[0066] The method for producing a molded product using the resin composition of the present embodiment is not particularly limited, and molding methods generally used for thermoplastic resins, such as injection molding, blow molding, extrusion molding, and press molding, can be applied. In this case, the particularly preferred molding method is injection molding because of its good fluidity. In injection molding, it is preferable to control the resin temperature to 250 to 310°C.

[0067] <Application> The resin composition of the present embodiment is used for laser welding using a light source having a wavelength in the range of 800 to 1100 nm. One embodiment of the resin composition of the present embodiment is in the form of pellets. In the present embodiment, the molded article is preferably formed from a resin composition or pellets.

[0068] <Kit> The resin composition of this embodiment and a light-absorbing resin composition containing a thermoplastic resin and a light-absorbing dye are preferably used as a kit for laser welding using a light source having a wavelength in the range of 800 to 1100 nm. The wavelength of the light source is preferably in the range of 900 to 1100 nm, more preferably in the range of 1000 to 1100 nm, and even more preferably in the range of 1050 to 1100 nm. That is, the resin composition of the present embodiment included in the kit serves as a light-selectively transparent resin composition, and a molded article formed from such a light-selectively transparent resin composition serves as a light-selectively transparent resin member for laser light during laser welding, whereas a molded article formed from a light-absorbing resin composition serves as an absorbing resin member for laser light during laser welding. A laser welded product is formed from the kit of this embodiment.

[0069] <<Light-absorbing resin composition>> The light absorbing resin composition used in this embodiment contains a thermoplastic resin and a light absorbing dye, and may further contain other components such as a reinforcing filler. Examples of the thermoplastic resin include polyamide resin, olefin resin, vinyl resin, styrene resin, acrylic resin, polyphenylene ether resin, polyester resin, polycarbonate resin, polyacetal resin, etc., and from the viewpoint of good compatibility with the light selectively transmitting resin composition (resin composition of the present embodiment), polyamide resin, polyester resin, and polycarbonate resin are particularly preferred, and polyamide resin is more preferred. The thermoplastic resin may be one type or two or more types. The type of polyamide resin used in the light absorbing resin composition is not limited, but the above-mentioned xylylenediamine polyamide resin is preferred. Examples of the reinforcing filler include glass filler (preferably glass fiber), carbon fiber, silica, alumina, carbon black, and fillers capable of absorbing laser light, such as inorganic powder coated with a material that absorbs laser light, and preferably glass filler, more preferably glass fiber. The glass filler is synonymous with the glass filler that may be blended in the resin composition of the present embodiment, and the preferred range is also the same. The content of the reinforcing filler is preferably 20 to 70 mass%, more preferably 25 to 60 mass%, and further preferably 30 to 55 mass%. The light absorbing dye includes a dye having an absorption wavelength in the range of the wavelength of the irradiated laser light, for example, in the range of 900 nm to 1100 nm in this embodiment. The light absorbing dye also includes a dye having a transmittance of less than 30%, or even 10% or less, when mixed in an amount of 0.3 parts by mass with respect to 100 parts by mass of polyamide resin and the light transmittance is measured. Specific examples of light absorbing pigments include inorganic pigments (black pigments such as carbon black (e.g., acetylene black, lamp black, thermal black, furnace black, channel black, ketjen black, etc.), red pigments such as iron oxide red, orange pigments such as molybdate orange, and white pigments such as titanium oxide), and organic pigments (yellow pigments, orange pigments, red pigments, blue pigments, green pigments, etc.). Among them, inorganic pigments are generally preferred because of their strong hiding power, and black pigments are more preferred. Two or more of these light absorbing pigments may be used in combination. The content of the light absorbing pigment is preferably 0.01 to 30 parts by mass relative to 100 parts by mass of the polyamide resin.

[0070] In the above kit, it is preferable that 80% by mass or more of the components in the resin composition other than the light-selective transmitting dye and reinforcing filler are common to the components in the light-absorbing resin composition other than the light-absorbing dye and reinforcing filler, more preferably 90% by mass or more of the components in the light-absorbing resin composition other than the light-absorbing dye and reinforcing filler, and even more preferably 95 to 100% of the components in the light-absorbing resin composition other than the light-absorbing dye and reinforcing filler are common to the components in the above kit.

[0071] <<Laser welding method>> Next, the laser welding method will be described. In this embodiment, a molded article (light selectively transmitting resin member) formed from the resin composition of this embodiment and a molded article (light absorbing resin member) formed from the light absorbing resin composition can be laser welded to produce a molded article (laser welded article). By laser welding, the light selectively transmitting resin member and the light absorbing resin member can be firmly welded without using an adhesive. Here, the light source used for the laser welding is a laser with a wavelength in the range of 800 to 1100 nm. The shape of the member is not particularly limited, but since the members are used by joining them together by laser welding, the shape usually has at least a surface contact portion (flat surface, curved surface). In laser welding, the laser light transmitted through the light selectively transparent resin member is absorbed by the absorbing resin member, melts, and the two members are welded together. The molded product formed from the resin composition of this embodiment has high transparency to laser light of a specific wavelength, so it can be preferably used as a light selectively transparent resin member. Here, the thickness of the member through which the laser light transmits (thickness in the laser transmission direction at the part through which the laser light transmits) can be appropriately determined taking into consideration the application, the composition of the resin composition, and other factors, and is, for example, 5 mm or less, preferably 4 mm or less.

[0072] As described above, the laser light source used for laser welding is a light source with a wavelength in the range of 800 to 1100 nm, preferably a laser with a wavelength in the range of 900 to 1100 nm, more preferably a laser with a wavelength in the range of 1000 to 1100 nm, and even more preferably a laser with a wavelength of 1050 to 1100 nm. The transmissive resin member and the absorptive resin member may be laser welded by any known laser welding method, but are suitable for galvano scanning type laser welding. Galvano scanning type laser welding, also known as quasi-simultaneous welding, is a method in which a laser beam is scanned with a built-in galvanometer mirror. By using galvano scanning type laser welding, the entire welded part is heated almost simultaneously, so the residual stress of the resulting laser welded product tends to be smaller. For details of the galvano scanning laser welding, please refer to the description in JP 2022-11052 A, the contents of which are incorporated into this specification.

[0073] More specifically, for example, when welding a light selectively transmitting resin member and an absorbing resin member, first, the parts to be welded of both are brought into contact with each other. At this time, the welded parts of both are preferably in surface contact, and may be flat surfaces, curved surfaces, or a combination of flat surfaces and curved surfaces. Next, a laser beam is irradiated from the light selectively transmitting resin member side. At this time, if necessary, a lens may be used to focus the laser beam on the interface between both. The focused beam passes through the light selectively transmitting resin member, is absorbed near the surface of the absorbing resin member, generates heat, and melts. Next, the heat is transmitted to the light selectively transmitting resin member by thermal conduction, melts it, forms a molten pool at the interface between both, and after cooling, the two are joined. There is also a method in which a protrusion such as an energy director or rib is provided, and the amount of sinking during welding is controlled for welding. The molded product in which the light selectively transmitting resin member and the light absorbing resin member are welded in this manner has high weld strength. Note that the molded product in this embodiment is intended to include not only finished products and parts, but also members that form part of these products and parts.

[0074] The molded product obtained by laser welding in this embodiment can be used in various applications, such as various storage containers, electrical and electronic equipment parts, office automation (OA) equipment parts, home appliance parts, machine mechanism parts, vehicle mechanism parts, etc. In particular, it can be suitably used in food containers, pharmaceutical containers, oil and fat product containers, hollow vehicle parts (various tanks, intake manifold parts, camera housings, etc.), vehicle electrical parts (various control units, ignition coil parts, etc.), advanced driver assistance system (ADAS) related parts, motor parts, various sensor parts, connector parts, switch parts, breaker parts, relay parts, coil parts, transformer parts, lamp parts, etc. In particular, the resin composition or kit of this embodiment is suitable for advanced driver assistance system (ADAS) related parts (particularly vehicle-mounted camera parts). As related components used in an ADAS (Advanced Driver Assistance System), there are cameras for image data, lidars and millimeter-wave radar components for distance data, GPS and odometer components for position data, and IMU (Inertial Measurement Unit) components for speed, acceleration, and attitude data, etc.

Example

[0075] The present invention will be further specifically described with reference to the following examples. The materials, usage amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed as long as they do not deviate from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. When it is difficult to obtain the measuring instruments used in the examples due to decommissioning or the like, measurements can be made using other devices having equivalent performance.

[0076] 1. Raw materials MP10: Polyamide resin (polymetaphenylene sebacamide), synthesized by the following method. <Synthesis example of MP10> Sebacic acid was heated and dissolved in a reaction vessel under a nitrogen atmosphere. Then, while stirring the contents, a mixed diamine with a molar ratio of 3:7 of p-xylenediamine (manufactured by Mitsubishi Gas Chemical Co., Inc.) and m-xylenediamine (manufactured by Mitsubishi Gas Chemical Co., Inc.) was gradually dropped under pressure (0.35 MPa) so that the molar ratio of diamine to sebacic acid became approximately 1:1, and the temperature was raised to 240 °C over 2 hours. After the dropping was completed, the internal temperature was raised. When it reached 250 °C, the pressure inside the reaction vessel was reduced to 0.08 MPa, and the internal temperature was further raised to continue the melt polycondensation reaction at 255 °C for 20 minutes to adjust the amount of components with a molecular weight of 1,000 or less. After the reaction was completed, the system was pressurized with nitrogen, and the contents were taken out in a strand shape and pelletized with a pelletizer to obtain a polyamide resin. The phosphorus atom concentration was 250 ppm by mass.

[0077] Talc: Micron White #5000S, manufactured by Hayashi Kasei Co., Ltd. PPE: Polyphenylene ether resin, PX100L, manufactured by Polyxylenol Singapore Pte. Ltd. Phosphazene flame retardant: FP-110, manufactured by Mitsui Fine Chemicals Maleic anhydride: CRYSTAL MAN AB, NOF Corporation Zinc borate: Firebreak AB, manufactured by Hayakawa Shoji Co., Ltd. Release agent: Calcium montanate, CS8CP, manufactured by Nitto Kasei Kogyo Co., Ltd. Perylene pigment: A mixture of the cis and trans isomers of the following compounds, pigments [ka] Comparison dye: A mixture of three colors: LTW-8701H, Solvent Red 179, Solvent Yellow 163, and Acid Blue 80. Glass fiber: ECS03T-296H, manufactured by Nippon Electric Glass Co., Ltd.

[0078] 2. Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 <Production of flame retardant master batches> 34.72 parts by mass of PPE, phosphazene flame retardant, zinc borate, and maleic anhydride in the amounts (parts by mass) shown in Table 1 were charged all at once into a Henschel mixer (forced mixing device with blades) and stirred for 2 minutes to obtain a blend. This blend was charged from the screw root of an extruder (TEM26SS manufactured by Shibaura Machine Co., Ltd.) using a two-screw cassette weighing feeder (CE-W-1-MP manufactured by Kubota Corporation) and melt-kneaded. The temperature setting of the extruder was 265°C. The strands coming out of the die outlet were cut and pelletized with a pelletizer to obtain a flame retardant master batch.

[0079] <Production of Resin Composition> The flame retardant master batch obtained above and the remaining PPE, MP10, talc, release agent, and pigment used in the master batching, which are the components shown in Table 1, were weighed out in the proportions shown in Table 1 (units are parts by mass), and then dry-blended. Then, the mixture was added from the screw root of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) using a twin-screw cassette weighing feeder (Kubota Corporation, CE-W-1-MP). Glass fibers were added from the side of the extruder using a vibration cassette weighing feeder (Kubota Corporation, CE-V-1B-MP), and melt-kneaded with the resin components, etc. to obtain pellets (resin composition). The temperature of the extruder was set to 280°C. However, in Comparative Example 2, none of the components were made into a master batch, and each component was directly charged and melt-kneaded. The pellets obtained above were each dried at 120°C for 4 hours, and then test pieces with thicknesses of 0.75 mm, 1.0 mm, and 1.5 mm were produced using an injection molding machine (SE-50D, manufactured by Sumitomo Heavy Industries, Ltd.) The molding was performed at a cylinder temperature of 280°C and a mold surface temperature of 110°C.

[0080] <Light transmittance> The test piece (1.0 mm thick) obtained above was measured for light transmittance (unit: %) at wavelengths of 940 nm and 1070 nm in accordance with ISO 13468-2. The measurement was performed using a transmittance measuring device on the side opposite the gate of the test piece. The transmittance measurement device used was a UV-3600 Plus manufactured by Shimadzu Corporation.

[0081] <Flame retardancy> The test pieces (0.75 mm, 1.0 mm, and 1.5 mm thick) obtained above were evaluated for flame retardancy in accordance with the UL-94 combustion test.

[0082] [Table 1]

[0083] As is clear from the above results, the resin composition of the present invention has a low light transmittance at a wavelength of 940 nm and is excellent in shielding. In addition, the resin composition of the present embodiment has a high light transmittance at a wavelength of 1070 nm and is excellent in laser weldability. Furthermore, the resin composition of the present embodiment has excellent flame retardancy.

Claims

1. A resin composition comprising a polyamide resin, a maleic anhydride-modified polyphenylene ether resin, a phosphazene-based flame retardant, a zinc metal oxide, and a colorant having a perylene skeleton, wherein the resin composition, when molded into a thickness of 1 mm, has a transmittance at a wavelength of 940 nm as measured in accordance with ISO 13468-2 of less than 20%, and the resin composition is suitable for laser welding using a light source having a wavelength in the range of 800 to 1100 nm.

2. The resin composition according to claim 1 , wherein the dye having a perylene skeleton has a naphthylenebenzimidazoperylene skeleton.

3. The resin composition according to claim 1 or 2, wherein the polyamide resin comprises a semi-aromatic polyamide resin.

4. The polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. The resin composition according to claim 1 or 2.

5. 3. The resin composition of claim 1 or 2, wherein the zinc metal oxide comprises zinc borate.

6. The resin composition according to claim 1 or 2, further comprising a glass filler.

7. the dye having a perylene skeleton has a naphthylenebenzimidazoperylene skeleton, the polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, 50 mol % or more of the diamine-derived structural units being derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units being derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; the zinc metal oxide comprises zinc borate; The resin composition according to claim 1 , further comprising a glass filler.

8. 8. The method for producing a resin composition according to claim 1, comprising forming a masterbatch of a phosphazene-based flame retardant using a maleic anhydride-modified polyphenylene ether-based resin, and then kneading the masterbatch with a polyamide resin.

9. A pellet of the resin composition according to claim 1, 2 or 7.

10. A molded article formed from the resin composition according to claim 1, 2 or 7.

11. A molded article formed from the pellets of claim 9.

12. A kit for laser welding using a light source having a wavelength in the range of 800 to 1100 nm, comprising the resin composition according to claim 1, 2 or 7, and a light-absorbing resin composition comprising a thermoplastic resin and a light-absorbing dye.

13. 13. A laser welded article formed from the kit of claim 12.

14. A method for producing a laser welded product, comprising laser welding the molded product according to claim 10 and a molded product formed from a light absorbing resin composition containing a thermoplastic resin and a light absorbing dye, wherein a light source used for the laser welding is a laser having a wavelength in the range of 800 to 1100 nm.

Citation Information

Patent Citations

  • Polyamide resin composition, kit, method for producing molding and molding

    JP2020012093A